Application of Rice-Husk Biochar to Coarse-Textured Ultisols and the Effects on Soil Fertility Indicators at Different Amendment-to-Sampling Intervals - Obalum, Sunday E.; Ebido, Nancy Ekene; Awaogu, Chukwuebuka Ebuka; Akubue, Jacinta Chinonso; Ozongwu, Ogorchukwu Valeria; Unagwu, Benedict Onyebuchi; Igwe, Charles Arizechukwu (UNIVERSITY OF LAMPUNG, 2025)
The low fertility status of the highly weathered tropical soils offers the opportunity to study the potential and optimum application rate of biochar as an organic soil amendment, especially for the dominant coarse-textured Ultisols. Despite the relatively fast mineralisation of organics in these soils and the need to synchronise nutrient release crops critical stages of nutrient requirement, the time corresponding to peak effects of biochar remains unclear. The effects of rice-husk biochar (RHB) on the soil fertility of sandy-loam Ultisols at 0, 7.5, 15, 30, and 60 Mg ha-1 equivalents in 2-kg soils were assessed at 0, 2, 4, 8, and 12 weeks of incubation (WOI). Treatments were prepared in batches to enable concurrent sampling for all five incubation intervals. The RHB enhanced soil fertility across the incubation intervals, with optimal rates as 15 Mg ha-1 for soil pH and 30 - 60 Mg ha-1 for macronutrients availability. Relative to the its non-application, RHB increased soil pH-H2O, total N, available P, exchangeable bases, exchangeable acidity, apparent CEC and base saturation by 4-30%, 43-100%, 30-202%, 13-240%, 14-675%, 21-126% and 7-82%, respectively. Soil pH tended to decrease after, while available P progressively decreased before 8 WOI, when treatment effects were generally most pronounced. At an all-encompassing optimal rate range of 30-60 Mg ha-1, RHB could reduce soil acidity and enhance the macronutrient status of coarse-textured Ultisols over at least 12 weeks, soil fertility restoration effects of which are likely to be most pronounced around 8 weeks.